In Vivo Function of Flow-Responsive Cis-DNA Elements of eNOS Gene: A Role for Chromatin-Based Mechanisms. Issue 5 (3rd August 2021) - Ku, Kyung Ha; Dubinsky, Michelle K.; Sukumar, Aravin N.; Subramaniam, Noeline; Feasson, Manon Y.M.; Nair, Ranju; Tran, Eileen; Steer, Brent M.; Knight, Britta J.; Marsden, Philip A.
Abstract : Background: eNOS (endothelial nitric oxide synthase) is an endothelial cell (EC)–specific gene predominantly expressed in medium- to large-sized arteries where ECs experience atheroprotective laminar flow with high shear stress. Disturbed flow with lower average shear stress decreases eNOS transcription, which leads to the development of atherosclerosis, especially at bifurcations and curvatures of arteries. This prototypic arterial EC gene contains 2 distinct flow-responsive cis-DNA elements in the promoter, the shear stress response element (SSRE) and the KLF (Krüppel-like factor) element. Previous in vitro studies suggested their positive regulatory functions on flow-induced transcription of EC genes including eNOS. However, the in vivo function of these cis-DNA elements remains unknown. Methods: Insertional transgenic mice with a mutation at each flow-responsive cis-DNA element were generated using a murine eNOS promoter–β-galactosidase reporter by linker-scanning mutagenesis and compared with episomal-based mutations in vitro. DNA methylation at the eNOS proximal promoter in mouse ECs was assessed by bisulfite sequencing or pyrosequencing. Results: Wild type mice with a functional eNOS promoter–reporter transgene exhibited reduced endothelial reporter expression in the atheroprone regions of disturbed flow (n=5). It is surprising that the SSRE mutation abrogated reporter expression in ECs and was associated with aberrant hypermethylation at the eNOS proximal promoter (n=7). Reporter gene silencing was independent of transgene copy number and integration position, indicating that the SSRE is a critical cis-element necessary for eNOS transcription in vivo. The KLF mutation demonstrated an integration site–specific decrease in eNOS transcription, again with marked promoter methylation (n=8), suggesting that the SSRE alone is not sufficient for eNOS transcription in vivo. In wild type mice, the native eNOS promoter was significantly hypermethylated in ECs from the atheroprone regions where eNOS expression was markedly repressed by chronic disturbed flow, demonstrating that eNOS expression is regulated by flow-dependent DNA methylation that is region-specific in the arterial endothelium in vivo. Conclusions: We report, for the first time, that the SSRE and KLF elements are critical flow sensors necessary for a transcriptionally permissive, hypomethylated eNOS promoter in ECs under chronic shear stress in vivo. Moreover, eNOS expression is regulated by flow-dependent epigenetic mechanisms, which offers novel mechanistic insight on eNOS gene regulation in atherogenesis. Abstract : Supplemental Digital Content is available in the text.